(Middle school girls have inclinations towards mathematics) (Journal of the College of Basic Education, 2023)
The current research aims to identify the tendencies of middle school students towards mathematics. Each paragraph, which is (applies to me, is neutral, does not apply to me), was distributed to the four journals of the scale (students’ tendencies towards the nature of mathematics, the students’ tendencies towards enjoying mathematics, students’ tendencies towards learning mathematics, and students’ tendencies towards the mathematics teacher), and the verification of Validity and stability of the tool. And after the tool became ready for application, the student tendencies scale was applied to the research sample (middle school students), in the middle and secondary schools of the General Directorate of Education in Maysan Governorate, and then the appropriate statistical analyzes were conducted, and the researcher concluded that middle school students have inclinations towards mathematics, and concluded that Middle school students have tendencies towards mathematics, and towards each of the areas of tendencies towards mathematics, then put a number of recommendations and suggestions.